MORPHOLOGICAL UNITS IN THE WORKS OF HALIMA KHUDOYBERDIYEVA (American Journal of Interdisciplinary Research and Development, 2022)
In this article, the morphological units of Halima Khudoyberdiyeva's creative efforts, productions and works, mainly in her poems, are explained, to which factors these units belong, and what qualities are classified in the word device.